2014
DOI: 10.1096/fj.14-255620
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and CpG methylation of the Pomc promoter in offspring of high‐fat‐diet‐fed dams are not “reprogrammed” by regular chow diet in rats

Abstract: This study aimed to determine whether epigenetic malprogramming induced by high-fat diet (HFD) has an obesogenic effect on nonmated and mated female rats and their offspring. Further, it aimed to reprogram offspring's epigenetic malprogramming and phenotype by providing normal diet after weaning. Body weight (BW) was measured, and plasma and hypothalamic arcuate nuclei were collected for analysis of hormones, mRNA, and DNA CpG methylation of the promoter of Pomc, a key factor in control of food intake. In nonm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 45 publications
4
52
0
2
Order By: Relevance
“…A similar effect has been demonstrated in nulliparous female rats fed a high fat diet for a long period; despite significantly higher body weight and plasma leptin levels in these rats, they had relatively low POMC mRNA expression, which was associated with hypermethylation of the POMC promoter [84]. POMC neurons in the arcuate nucleus (ARC) regulate energy homeostasis by secreting α-melanocyte-stimulating hormone (α-MSH), which is derived from a POMC precursor, in response to leptin signalling.…”
Section: Epigenetic Regulation Of Leptin-related Signalling Pathways:supporting
confidence: 74%
“…A similar effect has been demonstrated in nulliparous female rats fed a high fat diet for a long period; despite significantly higher body weight and plasma leptin levels in these rats, they had relatively low POMC mRNA expression, which was associated with hypermethylation of the POMC promoter [84]. POMC neurons in the arcuate nucleus (ARC) regulate energy homeostasis by secreting α-melanocyte-stimulating hormone (α-MSH), which is derived from a POMC precursor, in response to leptin signalling.…”
Section: Epigenetic Regulation Of Leptin-related Signalling Pathways:supporting
confidence: 74%
“…This was unexpected since clear ABA effects on gene expression were shown, and previous studies revealed differences in this region in response to dietary modulations (Marco et al, 2014). Similarly differences in Crh expression were not related to changes in DNAm of the Crh promoter region.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, the offspring of dams exposed to a high-fat diet during pregnancy maintained an adverse metabolic profile and epigenetic changes through adulthood [20]. The mechanisms linking maternal malnutrition and excessive weight in pregnancy to later-life metabolic health of the offspring are unclear.…”
Section: Prenatal and Perinatal Obesity-sensitive Time Windowsmentioning
confidence: 99%